IMF Staff papers : Volume 27 No. 3. (IMF Staff Papers; IMF Staff Papers, 1980)
This paper analyzes the implications of credit policies for output and growth and how they relate to the development of the current account and overall balance of payments. The framework chosen for the analysis is one in which the availability of financing is a direct and major determinant of current and future production. The paper identifies three channels through which credit policies can affect production in the economy. The principal conclusions are that limiting the overall level of credit is not a panacea for balance of payments problems; considerations regarding the distribution and the use of credit are important; in the absence of distortions, the current account objectives are best served by permitting credit expansion and investment to take place in the sector with the highest productivity, independent of whether this sector produces traded goods or nontraded goods; and tight credit policies can endanger the current account objectives when prevailing distortions lead to a 'crowding out' of productive uses of credit.